2023
DOI: 10.3389/fphys.2023.1140359
|View full text |Cite
|
Sign up to set email alerts
|

Pedal cadence does not affect muscle damage to eccentric cycling performed at similar mechanical work

Abstract: Purpose: This study aimed to investigate muscle damage when performing equal mechanical work of fast and slow pedaling speed by eccentric muscle actions (ECCs) cycling.Methods: Nineteen young men [mean ± standard deviation (SD) age: 21.0 ± 2.2 years; height: 172.7 ± 5.9 cm; and body mass: 70.2 ± 10.5 kg] performed maximal effort of ECCs cycling exercise with fast speed (Fast) and slow speed trials (Slow). First, subjects performed the Fast for 5 min by one leg. Second, Slow performed until the total mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The condition at 35 rpm was kept the same, and in a second condition, participants had to maintain maximal ECC pedaling exercise at 5 rpm until they had completed the same amount of work. They showed that the exercise at 5 rpm lasted five times longer than the condition at 35 rpm, but in this context, the decrease in MVC torques, as well as the markers of muscle damage, was similar between the two cadences used (13). Unfortunately, a 5-min or prolonged maximal exercise used in those studies (12,13) did not reflect the rehabilitation program for patients that generally lasts around 30 min at submaximal intensity.…”
mentioning
confidence: 98%
“…The condition at 35 rpm was kept the same, and in a second condition, participants had to maintain maximal ECC pedaling exercise at 5 rpm until they had completed the same amount of work. They showed that the exercise at 5 rpm lasted five times longer than the condition at 35 rpm, but in this context, the decrease in MVC torques, as well as the markers of muscle damage, was similar between the two cadences used (13). Unfortunately, a 5-min or prolonged maximal exercise used in those studies (12,13) did not reflect the rehabilitation program for patients that generally lasts around 30 min at submaximal intensity.…”
mentioning
confidence: 98%